KOMPETENSI PEGAWAI NON MEDIS DAN TINGKAT KEPUASAN MASYARAKAT - Valentina, Vina; Rusli, Zaili; R.F.S, Harapan Tua (Jurnal Ilmu Administrasi Negara, 2018)
Non-Medical Staff Competence and Public Satisfaction Level. This study aims to determine the influence of non-medical staff competence on the level of public satisfaction in hospitals Arifin Achmad Pekanbaru. The method used is descriptive and quantitative method. The sample is outpatient by 2016 at Arifin Achmad Hospital Pekanbaru as many as 100 people. Data collection techniques questionnaire, observation and interview. The types and sources of data used are primary and secondary data. The result of research has been done, then the conclusion that is t value is 6,400 while t-table is (0.05,99) = 1.6603 because t count (6,400)> from t table (1.6603) hence Ho significant. Thus variable employee competence (X) effect on the variable level of public satisfaction in hospitals Arifin Achmad Pekanbaru. From the calculation results obtained R2 value of 0.956 it shows 95.6% changes to employee competence factors to the level of public satisfaction in hospitals Arifin Achmad Pekanbaru while the other 4.4% is determined by other factors not observed in this study.